Performance of Aeration for Iron and Manganese Removal in Contaminated Well Water - Awang Pambagya Manggar Ingtyas; Farahdiba, Aulia Ulfah; Purnomo, Yayok Suryo (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Groundwater from dug wells is an important source for rural communities, but it often contains contaminants that exceed quality standards. One of the main problems is the high levels of iron (Fe) and manganese (Mn), which degrade water quality and pose health risks. This study aimed to evaluate the effectiveness of the aeration process in reducing Fe and Mn levels in contaminated well water. The experiment was conducted using a 20 L aeration tank with a contact time of 120 minutes. The water samples were analysed in an accredited laboratory before and after treatment. The results showed that aeration reduced Fe concentration from 1.03 mg/L to 0.50 mg/L (51% removal efficiency) and Mn from 5.86 mg/L to 1.85 mg/L (68% removal efficiency). Although the reductions were significant, the final concentrations of Fe and Mn still exceeded the quality standards set by Indonesian Ministry of Health Regulation No. 2 of 2023 (Fe = 0.2 mg/L; Mn = 0.1 mg/L). These findings indicate that aeration is effective as a low-cost and straightforward pretreatment for healthy water, but additional processes such as filtration or adsorption are required to achieve safe drinking water quality. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and Sanitation and SDG 3: Good Health and Well-beingSDG 11: Sustainable Cities and Communities